Syair Hamzah Fansuri sebagai Negasi Tuduhan Wahdatul Wujud - Widodo W; Muhamad Burhanudin; Siti Rohmah Soekarba; Yusro Edy Nugroho; Widodo W (Sutasoma : Jurnal Sastra Jawa, 2023)
This study explores the work of Hamzah Fansuri (HF) in the early vortex of the entry of Islam into the archipelago. The purpose of the analysis is to describe the various schools and views on the way religion developed through poetry and HF works. This research uses hermeneutics methods by reading, recording, and studying literature. The historical approach of the text is used by emphasizing the problem of wahdatul wujud. The research data is HF's work in the form of poems and books opposed by Nurudin Al-Raniri. The analysis is carried out by looking at the ideas, and concepts of HF's work. The results showed that HF's work was patterned Sufism not as a heresy. The accusation of deviant manifestation by Nur ad-Din Al-Raniri is untrue and tends to be forced. HF as a believer of wahdatul wujud recognizes the oneness of god. HF is not heterodox panties but adheres to mystical Sufism. Sufism HF is evidence of the symbol of Khaliq-Makluq to affirm the influence of the continuous current of Sufism in the network of Islamic intellectuals in the archipelago since the XVI century. The Book of Shaqāq al-Asyiqin formulates the Sufi path of Shari'a, Tariqat, Hakekat, and Makrifat while denying the notion that it is not a deviant form as alleged by Al-Raniri. Keywords: Hamzah Fansuri; Wahdatul Wujud; Sufism